ANALISIS SYARIAH TERHADAP PRODUK UANG ELEKTRONIK BANK SYARIAH - Zakiyah Zakiyah; Rahmatul Huda (Al-Iqtishadiyah: Ekonomi Syariah dan Hukum Ekonomi Syariah, 2017)
The following article explains about the congruence of electronic money products with the principles of syaria, especially those published by Islamic banking. Therefore, its needs to deep study of the topic, from several aspects; contract, transaction, and mechanism of syaria electronic money, so finally obtained the result of certainty and clarify about the congruence of electronic money with the principles of syariah. Because the implementation of the results of this study is needed by the Indonesia muslim society, especially those who has a strong religious commitment to practice the teaching of syaira in their life.